Multicultural foods - Video Education Australasia; Russell, Geoff (Australia: Video Education Australasia, 2022)
Examines five popular foods found in most Australian cities: French, Greek, Chinese, Indian, and Italian. At selected restaurants in two cities, we see how several traditional main course meals are prepared.